2014
DOI: 10.17306/j.afs.2014.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Milk proteins-derived bioactive peptides in dairy products: molecular, biological and methodological aspects

Abstract: Proteins are one of the primary components of the food, both in terms of nutrition and function. They are main source of amino acids, essential for synthesis of proteins, and also source of energy. Additionally, many proteins exhibit specifi c biological activities, which may have effect on functional or pro-health properties of food products. These proteins and their hydrolysis products, peptides, may infl uence the properties of food and human organism. The number of commercially available food products cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 98 publications
0
56
0
3
Order By: Relevance
“…FitzGerald, et al [68] exploited the hypotensive peptides from milk proteins and reported some examples of hypotensive dairy protein-derived products on the market such as a sour milk named "Calpis" (Calpis Co., Tokyo, Japan) or a fermented milk called "Evolus ® " (Valio Oy, Helsinki, Finland) containing IPP and VPP peptides (peptides with hypotensive effect) from β-and κ-casein. CalpisTM and Evolus ® have been tested extensively in rats and in a clinical trial [69].…”
Section: Applicationsmentioning
confidence: 99%
“…FitzGerald, et al [68] exploited the hypotensive peptides from milk proteins and reported some examples of hypotensive dairy protein-derived products on the market such as a sour milk named "Calpis" (Calpis Co., Tokyo, Japan) or a fermented milk called "Evolus ® " (Valio Oy, Helsinki, Finland) containing IPP and VPP peptides (peptides with hypotensive effect) from β-and κ-casein. CalpisTM and Evolus ® have been tested extensively in rats and in a clinical trial [69].…”
Section: Applicationsmentioning
confidence: 99%
“…Whey proteins were found to inhibit the growth of tumors more effectively than other food proteins. Food protein peptides can lower blood pressure, inhibit the activity of proline-specific endo-peptidases, stimulate the immune system, act as opioids and opioid antagonists, contract smooth muscles, inhibit blood platelet aggregation, inhibit HIV proteinase and oxidation processes, demonstrate antibacterial and fungicidal activity and surface activity, bind ions, participate in mineral transport, determine sensory properties, improve the nutritional value of foods and control body weight (Dziuba and Dziuba, 2014).…”
Section: Health Properties Of Whey Protein Fractionsmentioning
confidence: 99%
“…Contemporary consumers have a growing interest in foods which are not only a source of basic nutrition, which also delay and alleviate the consequences of lifestyle diseases (Dziuba and Dziuba, 2014). There is increasing interest in milk and particularly whey, as a potentially rich natural source of bioactive compounds to reduce disease risk and/or to prevent disease development (Huth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To date, immunomodulatory, antimicrobial, antithrombotic, opiate-like, mineral binding, antioxidative, antihypertensive, hypocholesterolemic and other effects have been discovered in a range of foods. In addition, many of the known bioactive peptides possess multifunctional properties, at least in vitro (Dziuba and Dziuba, 2014;FitzGerald and Murray, 2006;Korhonen and Pihlanto, 2006). This paper reviews the current knowledge about bioactive peptides derived from meat, with emphasis on their production and occurrence in fermented meat products and the potential benefi ts of these bioactive compounds to human health.…”
Section: Meat and Fermented Meat Products As A Source Of Bioactive Pementioning
confidence: 99%